New Technique for Gum Plastic Surgery with Single-Stage Implantation - Alisher Shavkatovich Akhrorov (Genius Publishing Group, 2024)
The doctor performing implantation must study the patient’s medical history in detail, as well as carry out all the necessary tests and examinations in a timely and high-quality manner. In addition to analyzing the blood taken from the patient, high and panoramic images also need to be taken. lower jaw using special stencils with regular size radio packet pins. This is necessary to determine the characteristics of anatomical formations.
Keywords: Wisdom teeth; crowded teeth; impacted teeth